Peran TPQ sebagai Lembaga Pendidikan Nonformal dalam Pembinaan Spiritual Anak di Masjid Al Ikhlas, Jalan Semangka 3, Kelurahan Panorama, Kecamatan Singgaran Pati - Alimni; Dalima Septiria; Andini Fadlillah; Sholiha Tussakdiah; Yesi Agustina (STKIP Subang, 2025)
This synthetic research aims to comprehensively analyze the role of the Al-Qur'an Education Park (TPQ) as a non-formal educational institution and explore an effective empowerment model for improving the spiritual quality and character development of children in Bengkulu City. This study integrates two research findings from different locations: the role of the Al Ikhlas Mosque TPQ in spiritual development and the empowerment model of the Nurul Ikhlas Mosque TPQ in Pagar Dewa. The synthesized approach includes descriptive-phenomenological qualitative research (the Al Ikhlas Study) and Participatory Action Research (PAR) (the Nurul Ikhlas Study). Data were collected through observation, in-depth interviews, and documentation. The synthesis results indicate that the TPQ plays a significant role, manifested through: (1) providing a cognitive and practical foundation for Islam (Tahsin and Storytelling), (2) internalizing morals through habits and creative methods such as role-playing, and (3) creating a communal religious environment (congregational prayer). Furthermore, the PAR-based empowerment model has proven effective in improving the quality of religious education by focusing on enjoyable, contextual learning methods (Tartil, memorization, daily worship practices), and adaptive (grouping based on ability). Despite facing constraints on facilities and parental involvement, collaborative solutions ensured the program's effectiveness and demonstrated the potential of TPQ (Islamic Religious Teaching and Learning) as a participatory and sustainable model for mosque empowerment in urban contexts.